If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = 2x + -2 Reorder the terms: 5x = -2 + 2x Solving 5x = -2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 5x + -2x = -2 + 2x + -2x Combine like terms: 5x + -2x = 3x 3x = -2 + 2x + -2x Combine like terms: 2x + -2x = 0 3x = -2 + 0 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667
| -m+2m+6=m+6 | | 3/4×y=6 | | 9x^2-10x=-1 | | y=1/3(9)-1 | | 4-2x=-5-5x | | 2x+5=250 | | y=1/3(3)-1 | | 5-(2x-3)=8+2x | | -13+3x=8x+8x | | -6z+6+7z=11 | | x^4-x^3-5x^2=0 | | 427-51x=180 | | 4x+7(x-9)=69 | | x+0.07x=282.68 | | -14-4r=-2+8r | | 6x+y=27 | | 7k+8+8k=11+5+4k+3k | | 5y-3y=27 | | 3x+7(5x-5)=193 | | 2t+-1=3t+7 | | 3b-5=-7+2b | | 5x+4y=63 | | 4f+x-4=-4 | | 18=-4x-5x | | 5x+6(3x-15)=117 | | 2x+2(2x+5)=250 | | 3x+5(0)=30 | | -x=15+30 | | -6=-4p+5p | | 1.50x+0.75=2.00x+0.50 | | 3x+5(-3)=30 | | -15=4b-b |